Using R for numerical analysis in science and engineering - Bloomfield, Victor A. (CRC Press, Taylor & Francis Group, 2014)
This book shows how the free and open-source R environment can be used as a powerful and comprehensive platform for the kinds of numerical analysis that are traditionally employed by MATLAB®. With R code fully integrated, the book offers brief descriptions of basic approaches and emphasizes detailed worked examples. It covers functions in the base installation of R as well as those in contributed packages